Stroke Rehabilitation Program in Improving ADL (Activity Daily Living): Literature Review - Miftafu Darussalam; Zahroh Shaluhiyah; Bagoes Widjanarko (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Background: One-third of stroke patients experience moderate to severe physical disorders, such as decreased independence in daily activities. Stroke therapy is vital in assisting stroke survivors in achieving optimal functional levels and preventing further functional loss. Objective: To see how stroke rehabilitation programs improve ADL (Activity Daily Living). Methods: There are six stages in this literature, including goal identification, literature selection using Prisma diagrams, data mapping by conducting critical appraisals based on the RCT research checklist, summarizing and reporting results, and expert consultation. Relevant literature was found using four databases, including JSTOR, Science Direct, ProQuest, and Cambridge core, using the keywords (stroke survivor) AND (rehabilitation program) AND (activities of daily living). Results: Literature obtained 186022 articles. Eight articles were selected for review. The intervention group in all articles showed a significant increase in ADL ability compared to the control group. Conclusion: Early rehabilitation management in acute stroke care is essential to optimize recovery potential and avoid secondary problems different from stroke sequelae. The improved physical recovery and daily functional abilities result from a rehabilitation program at a higher level of intensity and consistency. Abstrak: Latar belakang: Sepertiga penderita stroke mengalami gangguan fisik sedang hingga berat, seperti penurunan kemandirian dalam aktivitas sehari-hari. Terapi stroke sangat penting dalam membantu penderita stroke dalam mencapai tingkat fungsional yang optimal dan mencegah kehilangan fungsional lebih lanjut. Tujuan: untuk melihat bagaimana program rehabilitasi stroke meningkatkan ADL (Activity Daily Living). Metode: Ada enam tahapan dalam literatur ini, meliputi identifikasi tujuan, pemilihan literatur menggunakan diagram Prisma, pemetaan data dengan melakukan penilaian kritis berdasarkan checklist penelitian RCT, meringkas dan melaporkan hasil, dan konsultasi ahli. Literatur yang relevan ditemukan menggunakan empat database, termasuk JSTOR, Science Direct, ProQuest, dan Cambridge core, dengan menggunakan kata (stroke survivor) AND (rehabilitation program) AND (activities of daily living). Hasil: Literatur didapatkan 186022 artikel, 8 artikel terpilih untuk direview. Kelompok intervensi pada semua artikel menunjukkan peningkatan yang signifikan untuk kemampuan ADL dibanding dengan kelompok kontrol. Kesimpulan: Manajemen rehabilitasi dini dalam perawatan stroke akut sangat penting untuk mengoptimalkan potensi pemulihan dan menghindari masalah sekunder yang berbeda dari gejala sisa stroke. Peningkatan pemulihan fisik dan kemampuan fungsional sehari-hari adalah hasil dari program rehabilitasi pada tingkat intensitas dan konsistensi yang lebih tinggi.